2015
DOI: 10.12944/cwe.10.2.29
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Drinking Water from Dimapur District of Nagaland and Karbi-Anglong District of Assam for Possible Related Health Hazards

Abstract: Quality of drinking water always remains a sensitive issue since contaminants like Arsenic, Fluoride in excess amount cause serious health hazards. Arsenic in drinking water causes harm to physical and mental health of a person and this may even cause cancer and damage to blood vessels and heart. This may also cause reproductive problems and birth defects.Several states of India are known to be effected arsenic contaminated water which leads to serious illness. Uttar Pradesh, Bihar, Jharkhnad, West Bengal, Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Similarly, a study by Puzari et al. (2015) and NPCB (2018) reported As concentrations <10 μg/L in Dimapur, Nagaland, located at the southern tip of the Golaghat South subdistrict (Figure 3a). These studies support our prediction of a low probability of As >10 μg/L in groundwater in these areas.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, a study by Puzari et al. (2015) and NPCB (2018) reported As concentrations <10 μg/L in Dimapur, Nagaland, located at the southern tip of the Golaghat South subdistrict (Figure 3a). These studies support our prediction of a low probability of As >10 μg/L in groundwater in these areas.…”
Section: Resultssupporting
confidence: 55%
“…These areas are located at a higher elevation with greater slopes, and are thus favorable for greater aquifer flushing and unfavorable for As release to groundwater. Similarly, a study by Puzari et al (2015) and NPCB (2018) reported As concentrations <10 μg/L in Dimapur, Nagaland, located at the southern tip of the Golaghat South subdistrict (Figure 3a). These studies support our prediction of a low probability of As >10 μg/L in groundwater in these areas.…”
Section: Arsenic-hazard Probabilistic Zonesmentioning
confidence: 56%
“…The decisive reasons behind the deterioration of urban water, primarily are agricultural, urban conducts, input of untreated industrial as well as hospital effluents, domestic wastewater (like used detergent, excreta and faecal sludge), even uncontrolled landfills, thereby posing tremendous threat to human health [9].The unbalanced physico-chemical parameters and presence of harmful micro-organisms in drinking water are reasons behind causing several adverse effects in human body [10]. The ground water in North-Eastern states of India (especially Arunachal Pradesh, Assam and Nagaland), are usually found to be high on the iron and fluoride contents [11].The people from several parts of Assam are facing lots of struggles for a drop of good quality water [12]. The microbial contaminations of water sources are occurring manly due to the industrial waste and domestic waste, except the educated people the rural people are consuming this contaminated water without testing [13] [14].…”
mentioning
confidence: 99%